2016
DOI: 10.1016/j.virusres.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

JNK and p38 mitogen-activated protein kinase pathways contribute to porcine epidemic diarrhea virus infection

Abstract: The mitogen-activated protein kinase (MAPK) pathways, which are central building blocks in the intracellular signaling network, are often manipulated by viruses of diverse families to favor their replication. Among the MAPK family, the extracellular signal-regulated kinase (ERK) pathway is known to be modulated during the infection with porcine epidemic diarrhea virus (PEDV); however, involvement of stress-activated protein kinases (SAPKs) comprising p38 MAPK and c-Jun NH2-terminal kinase (JNK) remains to be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…8A and B), indicating p38 MAPK and SAPK/JNK can be activated during PEDV infection. However, the ratio of Bax/Bcl-2 showed little change following inhibitor treatment, in agreement with previous studies (Lee et al, 2016). Taken together, these results clearly indicate that the PEDV dependent ROS/p53 mediated pathway induced apoptosis in Vero cells whereas p38 MAPK and SAPK/JNK were not involved in apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…8A and B), indicating p38 MAPK and SAPK/JNK can be activated during PEDV infection. However, the ratio of Bax/Bcl-2 showed little change following inhibitor treatment, in agreement with previous studies (Lee et al, 2016). Taken together, these results clearly indicate that the PEDV dependent ROS/p53 mediated pathway induced apoptosis in Vero cells whereas p38 MAPK and SAPK/JNK were not involved in apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, cholesterol removal has been shown to result in the inhibition of cellular signaling pathways [53]. We previously found that PRRSV and PEDV activate specific intracellular signaling networks such as mitogen-activated protein kinase (MAPK) cascade pathways to favor replication of these viruses, but these signaling pathways are irrelevant to virus internalization [24,[28][29][30]. Based on these previous data, cellular cholesterol does not appear to act through MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 98%
“…It is worth pointing out that the increase in serum proinflammatory cytokine and chemokine levels in both PEDV infected suckling and weaned pigs mentioned above could reflect the outcome of the simultaneous induction of the key components of the mitogen-activated protein kinase (MAPK) cascade including Erk1/2 and JNK/p38 (116,117), and the activation of NF-κB pathway (72,118) during the PEDV infection. As shown in the context of other pathogenic infections (119,120), the concurrent activation of both MAPK components and the transcription factor NF-κB during PEDV infection might lead to the upregulation of both pro-inflammatory cytokines and chemokines.…”
Section: Cellular Innate Immune Responses To Pedv and Pdcovmentioning
confidence: 99%